Gender relations and couple negotiations of British men's food practice changes after prostate cancer. (1st January 2015) - Mróz, Lawrence W.; Robertson, Steven
Highlights: We explored how gender relations shaped couple food negotiations after prostate cancer. Deciding, implementing and monitoring diet change was shaped by traditional gender roles. Women filtered information, monitored men's diets and regulated diet exceptions. Diet interventions for men with prostate cancer must thoughtfully consider partners. Abstract: Nutrition plays an important role in the health of men diagnosed with prostate cancer and dietary interventions can therefore be a significant part of prostate cancer survivorship supportive care. Family food provision, however, involves complex social interactions, which shape how men engage with their diets and dietary interventions. The role that gender plays in shaping prostate cancer couples' food practices and men's diets after a prostate cancer diagnosis is thought to be important but is little understood. This study explored couples' accounts of nutrition information seeking and diet change to gain a better understanding of how gender relations shaped men's food practices after prostate cancer diagnosis. Qualitative health interviews with men and their partners were conducted and analysed using interpretive descriptive methods. Findings demonstrated how couples navigated food change journeys that involved seeking information, deciding what changes were warranted and implementing and regulating diet changes. Two overarching themes that illustrated couples' food negotiations were called 'Seeking information and deciding on food changes ' and 'Monitoring food changes '. Additional sub-themes described who led food changes, women's filtering of information, and moderation or 'treats'. Throughout these food change journeys, interactions between men and women were at play, demonstrating how gender relations and dynamics acted to shape couples' food negotiations and men's food practices. Findings reveal that attention to gender relations and the men's family food dynamics should inform diet interventions for men with prostate cancer in order to improve uptake.